HISTORICAL ROOTS OF TECHNICAL COMMUNICATION IN THE CHINESE TRADITION - DING, DANIEL (CAMBRIDGE SCHOLARS PUBLIS, 2020)
This book traces Chinese technical communication from its beginnings, investigating how it began and the major factors that shaped its practice. It also looks at the major philosophical and historical traditions in Chinese technical communication, and how historical and philosophical threads play out in contemporary Chinese technical communication practice. In considering such issues, the book gives attention to some of the major classical Chinese texts, but treats them as artefacts of technical communication. It explores the roots of Chinese technical communication, reviews traditional philos.